Integrating Biochemical and Computational Approaches Reveal Structural Insights in Trastuzumab scFv-Fc Antibody Engineering - Olga Bednova; Jessica Pougoue Ketchemen; Hazem Mslati; Mark Barok; Heikki Joensuu; Natalie Zeytuni; Francesco Gentile; Leon Sanche; Humphrey Fonge; Jeffrey Victor Leyton (Biomolecules)
Antibody-based agents have become a preferred treatment for various diseases, including cancer, due to significant advances in antibody engineering. The use of single-chain Fv-Fcs (scFv-Fcs) has been a promising engineering approach for therapeutic design. The concept is that the Fc provides increased stability and target binding and ultimately improves performance. However, the structural and dynamic relationship between the variable and Fc domains, which are fused in close proximity, and the impact on stability and target binding are not well understood. This study evaluated trastuzumab-derived scFv-Fc antibodies, focusing on the impact of their design on important biopharmaceutical parameters. Computational modelling and molecular dynamics, alongside experimental studies, were used to ascertain their dynamics, expression and purification, stabilities, and binding potencies. The results showed that the scFv subunits exhibited stochastic interplays that lead to diverse shapes and were associated with functional performance. This new understanding of scFv-Fc antibodies and their structural and functional nuances provides important details to further guide the design of more effective and less toxic therapeutics.